Exploring green purchasing intentions and behaviours among Vietnamese Generation Z: A perspective from the theory of planned behaviour. - Quang-Huy Ngo; Thanh-Dung Nguyen; Nhu-Binh Phan (PLoS ONE)
As environmental degradation escalates, the critical need to understand green purchasing intentions and behaviours among Vietnamese Generation Z becomes increasingly urgent. Although the Theory of Planned Behavior (TPB) has been extensively applied to study pro-environmental behaviours, there remain discrepancies in how green attitudes, green subjective norms, and green perceived behavioural control influence green purchasing intentions and green purchasing behaviours. This study aims to clarify these relationships within the unique socio-economic and cultural context of Vietnamese Generation Z, a demographic influenced by collectivistic cultural values, generational characteristics, and dynamic economic conditions. These factors may reshape the conventional dynamics of TPB. Utilising quantitative methodologies, this research analysed responses from 237 Vietnamese Generation Z consumers through structural equation modelling to assess the impacts of green attitude, green subjective norms, and green perceived behavioural control on green purchasing intentions and green purchasing behaviours, particularly focusing on the mediating role of green purchasing intentions. The findings demonstrate that green attitude, green subjective norms, and green perceived behavioural control significantly affect both green purchasing intentions and green purchasing behaviours, thereby confirming the mediating influence of green purchasing intentions. This research reaffirms TPB's relevance in Vietnam's distinct cultural and economic environment while contributing to the broader TPB literature by exploring the mediating effects among key variables. These results also underscore the need for policymakers and businesses to create community-oriented environmental programs and tailor marketing strategies to enhance pro-environmental purchasing among young consumers.